2004
DOI: 10.1136/ard.2003.012450
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab in spondyloarthropathy associated with Crohn's disease: an open study on the efficacy of inducing and maintaining remission of musculoskeletal and gut manifestations

Abstract: Objective: To evaluate the efficacy and tolerability of anti-tumour necrosis factor a (TNFa) monoclonal antibody (infliximab) in the treatment of spondyloarthropathy (SpA) associated with active and inactive Crohn's disease (CD). Methods: Twenty four patients with SpA associated with active or inactive CD (16 active, 8 quiescent) were treated with anti-TNFa monoclonal antibody (infliximab) with repeated infusions for a period of 12-18 months. The treatment aimed at ameliorating the general musculoskeletal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 25 publications
(23 reference statements)
2
61
0
2
Order By: Relevance
“…4,[17][18][19][20] A small (N ¼ 30) randomized controlled trial comparing infliximab to placebo for the treatment of pyoderma gangrenosum found a higher rate of clinical improvement at week 2 in the infliximab recipients (46% versus 6%, P ¼ 0.025), 21 although not all of the patients in this series had inflammatory bowel disease. A recent publication of an observational analysis of adalimumab use for CD in a referral center 22 found a meaningful rate of complete resolution of EIMs at week 4 (31.5%) and week 12 (41%).…”
Section: Discussionmentioning
confidence: 90%
“…4,[17][18][19][20] A small (N ¼ 30) randomized controlled trial comparing infliximab to placebo for the treatment of pyoderma gangrenosum found a higher rate of clinical improvement at week 2 in the infliximab recipients (46% versus 6%, P ¼ 0.025), 21 although not all of the patients in this series had inflammatory bowel disease. A recent publication of an observational analysis of adalimumab use for CD in a referral center 22 found a meaningful rate of complete resolution of EIMs at week 4 (31.5%) and week 12 (41%).…”
Section: Discussionmentioning
confidence: 90%
“…In this paper, Generini et al[ 38] described good axial and peripheral musculoskeletal pain control with infliximab in addition to the gastrointestinal improvement in 15 patients with active CD. In AS alone, infliximab and etanercept have now been approved, based on large placebo-controlled studies, for patients insufficiently treated with sulfasalazine and NSAIDs or intolerant of NSAIDs [39,40,41].…”
Section: Treatmentmentioning
confidence: 99%
“…Our findings are thus in keeping with other studies 44,50 . Anti-TNF therapy has been shown to induce and maintain remission of CD, while at the same time treating severe active SpA 51 , suggesting that it should be the preferred drug for the treatment of active and severe SpA associated with active or quiescent CD. These results are likely to have an important effect on the selection of anti-TNF therapy in patients with SpA.…”
Section: Kopylov Et Al: the Space Capsule Studymentioning
confidence: 99%